Internal profitability determinants of organic production companies in Republika Srpska - Galić, Jovana (Anali Ekonomskog fakulteta u Subotici, 2024)
The aim of this paper is to investigate the internal profitability determinants value and influence on profitability measured by return of assets of organic production companies in Republika Srpska. For this purpose, abbreviated balance sheets of 21 companies engaged in this type of agricultural production in period from 2014 to 2021 were provided. The results showed that the internal determinants of profitability age, liquidity ratio, debt measured by financial leverage, sales growth and capital turnover have a significant impact on profitability. While debt has negative correlation, other determinants have positive correlation.